STRATEGI PENATAAN PEDAGANG PELAKU USAHA KECIL DI AREA ENTROP JAYAPURA - Bless, Veralde Marthina; Rante, Harmonis; Rusim, Dewi Ana (Jurnal ELIPS (Ekonomi, Lingkungan, Infrastruktur, Pengembangan Wilayah, dan Sosial Budaya), 2023)
The uncontrolled development of street vendors makes them occupy every empty space in the city even if it is a public facility. The street vendors illegally sell almost all pedestrian paths, open spaces, green lanes and other urban spaces. The existence of street vendors has positive and negative sides, thus making the existence of street vendors a dilemma for the city government in arranging them One of the trading areas in Jayapura City that is widely occupied by street vendors is the Entrop area. This area is located between Jayapura and Abepura, so its position becomes strategic. The subjects referred to in this study are street vendors located along Jl. Kelapa Dua, Entrop, Jayapura City. The analysis method used in this study is a qualitative approach where research on data, findings and visualization in the field is carried out by prioritizing description, explanation and comparison which includes descriptive, assumptive, and normative. The street vendors operating in Entrop often occupy locations that are not actually intended for street vendors. The location used is the shoulder of the road along Jln. Kelapa Dua, Entrop Village, South Jayapura District, Jayapura City. Solutions that can be done to provide effective space and space to street vendors in Entrop, Jayapura City are regional planning by involving all regional stakeholders, relocating street vendors into the market and increasing the knowledge and participation of street vendors in waste processing.